ANALYSIS AND EVALUATION OF THE PERFORMANCE EFFICIENCY OF MICRO-AGRICULTURAL PROJECTS IN LATTAKIA GOVERNORATE - SYRIA DURING THE 2022-2023 SEASON - R. A. Muslim; I. H. Saqr; A. S. Ahmed (مجلة الأنبار للعلوم الزراعية, 2025)
The study was conducted in Lattakia Governorate, Syria, during the 2022-2023 season, where the total size of the studied community was 2861 projects. A questionnaire was designed and distributed to a random sample of 303 micro-agricultural projects in the areas affiliated with Lattakia Governorate. Efficiency was evaluated using the three-point Likert scale and applying some economic efficiency indicators. The research aimed to evaluate the performance efficiency of micro-agricultural projects in Lattakia Governorate in terms of economic, environmental, learning, and growth dimensions and identify the most prominent difficulties facing agricultural producers. The results showed a statistically significant relationship at a significance level of 0.05 between the project's economic, environmental, learning and growth dimensions and its performance efficiency. The results of evaluating the studied projects also showed good economic efficiency, with a general average of 2.47 and a relative importance of 82.24%, medium environmental efficiency, with an average of 2.23 and a relative importance of 74.50%, and good learning and growth efficiency with an average of 2.47 and a relative importance of 82.35%, for the studied projects in light of price fluctuations and limited resources. The research recommended issuing legislation and supportive policies to enhance micro-agricultural entrepreneurship and providing specialized financing institutions for soft loans to small farmers